2021
DOI: 10.1097/prs.0000000000007957
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Farkas: Updating Cephalic Index Norms in a Large, Diverse Population

Abstract: ephalic index is the ratio between head width, the biparietal diameter, and head length, the anteroposterior diameter. Cephalic index can be obtained through the use of a manual caliper, skull radiography, computed tomography, or three-dimensional computed tomographic imaging. Cephalic index is a key measure that guides management of positional plagiocephaly, which is occipital flattening because of time spent on the back in infancy. The effect of supine sleeping on molding of the occipital skull is greatest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 21 publications
(27 reference statements)
2
30
1
Order By: Relevance
“…Littlefield reported that the probability of re-surgery for patients with craniosynostosis increases if postoperative CROs are not administered. 17 In the current study, despite a remarkable decrease in CI value from 130% to 98%, based on the reported normal CI value of 82% to 83% for age-matched children, 15 this remains outside the normal range. According to the head proportional measurements, specifically the CI, and personal judgment from a cosmetic point of view, the skull's symmetry improvement is optimum in most cases with sagittal synostosis and relatively good in those with bilateral coronal synostosis.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Littlefield reported that the probability of re-surgery for patients with craniosynostosis increases if postoperative CROs are not administered. 17 In the current study, despite a remarkable decrease in CI value from 130% to 98%, based on the reported normal CI value of 82% to 83% for age-matched children, 15 this remains outside the normal range. According to the head proportional measurements, specifically the CI, and personal judgment from a cosmetic point of view, the skull's symmetry improvement is optimum in most cases with sagittal synostosis and relatively good in those with bilateral coronal synostosis.…”
Section: Discussioncontrasting
confidence: 54%
“…CI is derived from the cranial width to cranial length ratio multiplied by 100, and its normal range varies from 82% to 83%. 15 CVAI is the difference between the long and short cranial diagonal diameter divided by the long diagonal diameter multiplied by 100, and a CVAI of less than 3% is deemed normal. 1 After fitting the CRO, we measured and recorded the anthropometric values of the patient's skull with a measuring tape and a caliper at each visit.…”
Section: Surgical Intervention and Cro Fitting Processmentioning
confidence: 99%
“…Also notably, it would not appear that the higher average cephalic index of Asian individuals leads this population to have a differing perception of ideal head shape. 6,8 Differences were not found between males and females, and it would appear that perception of head shape is independent of gender identity. However, only 8 of the respondents identified as non-binary, and so further study is required regarding this population before definitive statement can be made.…”
Section: Discussionmentioning
confidence: 73%
“…This normative data was obtained in a small Caucasian population (0-6 months, N = 87) prior to the Back to Sleep campaign. In 2019, a cross-sectional study of a larger (0-6 months, N = 357) and more ethnically-diverse population, performed by Phelan et al 6 (UMass) , has challenged the longstanding normative values for cephalic index finding the average for the 0 to 6 month age group to be 83.5 ± 5.9. It remains unanswered whether this new mean CI is supported by a perception of what is normal or preferred.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Optimal treatment timing takes advantage of the rapid growth phase of the brain, which normally decelerates with time. 13,14 Severity of deformation is important in guiding treatment choice and is typically measured by cephalic index and cranial vault asymmetry index (CVAI). 15,16…”
mentioning
confidence: 99%